Is Egypt on a Sustainable Path of Debt Repayment: Evidence from IMF Framework and Fiscal Reaction Function - Rashied, Maha (AUC Knowledge Fountain, 2021)
Fiscal policy is the starting point for an economy to achieve solid economic and social objectives through macroeconomic stability. Risks associated with excessive borrowing and the required fiscal adjustments are threatening especially to developing countries whose debt to GDP ratios are on the rise. Those countries’ fiscal policies’ sustainability is questioned; hence this research aims at testing for Egypt public debt sustainability and assessing the method capitalized on by the Egyptian authorities; the IMF Approach. By comparing the IMF Debt Sustainability Analysis Approach to the fiscal reaction function with ARDL and VAR as estimation methods, the results of both methods indicate weak sustainability of the public debt. However, the basis on which the conclusion is built differ tremendously. Areas where the IMF Framework exercises several limitations are also highlighted and critiqued. This thesis uses quarterly time-series data set from Q3-2005 to Q2-2020 in evaluating the government’s reaction to public debt accumulation. The policy implications of the thesis point out to the importance of the necessary departure from the IMF Approach as the only tool that judges Egypt public debt sustainability and the need to integrate other measures as it juxtaposes the concerns needed to be taken care of. Calls for fiscal transparency and governance, as well as public expenditure reforms are also required. JEL Classification Codes: E62, H62, H63, F34